Longitudinal and Cross-Sectional Cultural Developments - Nicolau, Felix (Swedish Journal of Romanian Studies, 2018)
Romulus Bucur is a renowned writer and literary critic. He is also faculty member at Transylvania University of Braşov, institution well-known for its courses of creative writing and translation studies. “Glosses” is a nimbly written theoretical book wherein many topics are analyzed. One of the most important is the work of Alexandru Muşina, editor, writer, professor, and mentor of the Group of Braşov (a fertile contingent of writers still holding sway in Romanian literature). The second part of the volume is dedicated to the Romanian translations from the classical and contemporary Chinese culture. Mention must be made about the semiotic approach to all literary works glossed about.